A fly-by-wireless UAV platform based on a flexible and distributed system architecture - Afonso, José A. (2006)
This paper reports and describes the diverse stages concerning the development of an unmanned aerial vehicle (UAV) named “Aeronave Inteligente com Visão Artificial”, better known by its acronym as AIVA. The design and development of the first aerial platform, the onboard ommunications, the instrumentation system, the bidirectional communications platform to/from ground station, the flight control system, the navigation strategies, as well as the vision systems to help navigation and to carry out the planned surveillance missions, are addressed in this paper. One of the main innovative issues of this platform is the distributed onboard wireless network, based on Bluetooth technology and on a multiprocessor architecture system. These features increase the platform flexibility. The goals already accomplished so far reveal interesting developments to be used successfully in commercial UAV platforms.